Biomarkers in Immunotherapy-Based Precision Treatments of Digestive System Tumors - Zeng, Zhu; Yang, Biao; Liao, Zhengyin (Frontiers in Oncology, 2021)
Immunotherapy, represented by immune checkpoint inhibitors (mainly referring to programmed death-1 (PD-1)/programmed death-ligand 1 (PD-L1) blockades), derives durable remission and survival benefits for multiple tumor types including digestive system tumors [gastric cancer (GC), colorectal cancer (CRC), and hepatocellular carcinoma (HCC)], particularly those with metastatic or recurrent lesions. Even so, not all patients would respond well to anti-programmed death-1/programmed death-ligand 1 agents (anti-PD-1/PD-L1) in gastrointestinal malignancies, suggesting the need for biomarkers to identify the responders and non-responders, as well as to predict the clinical outcomes. PD-L1expression has increasingly emerged as a potential biomarker when predicting the immunotherapy-based efficacy; but regrettably, PD-L1 alone is not sufficient to differentiate patients. Other molecules, such as tumor mutational burden (TMB), microsatellite instability (MSI), and circulating tumor DNA (ctDNA) as well, are involved in further explorations. Overall, there are not still no perfect or well-established biomarkers in immunotherapy for digestive system tumors at present as a result of the inherent limitations, especially for HCC. Standardizing and harmonizing the assessments of existing biomarkers, and meanwhile, switching to other novel biomarkers are presumably wise and feasible.